2013
DOI: 10.1016/j.scitotenv.2012.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Phototransformation rate constants of PAHs associated with soot particles

Abstract: Photodegradation is a key process governing the residence time and fate of polycyclic aromatic hydrocarbons (PAHs) in particles, both in the atmosphere and after deposition. We have measured photodegradation rate constants of PAHs in bulk deposits of soot particles illuminated with simulated sunlight. The photodegradation rate constants at the surface (k0p), the effective diffusion coefficients (Deff), and the light penetration depths (z0.5) for PAHs on soot layers of variable thickness were determined by fitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…It has been proposed in the literature that suspended particulate matter can influence the photodegradation rate of PAHs by hindering the light intensity and photosensitizing humic acid contained in the suspended particulate matter (Xia et al 2009;Dong et al 2010;Kim et al 2013). According to Fig.…”
Section: The Influence Of Salinity On Pah Photodegradationmentioning
confidence: 99%
“…It has been proposed in the literature that suspended particulate matter can influence the photodegradation rate of PAHs by hindering the light intensity and photosensitizing humic acid contained in the suspended particulate matter (Xia et al 2009;Dong et al 2010;Kim et al 2013). According to Fig.…”
Section: The Influence Of Salinity On Pah Photodegradationmentioning
confidence: 99%
“…This reflects greater divergence in the spatial distribution of An/(An + Phe), which can be attributed to several causes. According to a previous study, the overall rate of photodegradation of irradiated 2-3-ring PAHs on soot particles is affected by fast photolysis and fast diffusion kinetics, while that of PAHs with 4 or more rings is evidently governed by either the combination of slow photolysis and slow diffusion kinetics, or by extremely slow diffusion kinetics alone (Kim et al, 2013). Therefore, the comparatively high COD value of An/ (An + Phe) reflects the greater fragility of these LMW congeners in comparison with those of Fluo and Pyr.…”
Section: Inter-site Comparison Of Coefficient Of Divergence (Cod)mentioning
confidence: 92%
“…A study by Kim et al (2013) highlighted the importance of both fast photodegradation and fast diffusion kinetics on the reduction of LMW PAHs (with 2-3 rings) in comparison with HMW PAHs (with 4 or more rings). Although the photodegradation rates of 16 U.S. EPA-priority PAHs follow first-order kinetics, UV-B (315-280 nm) exposure can dramatically accelerate the photolysis rate of PAHs adsorbed onto fly ash particles (Niu et al, 2007).…”
Section: Effects Of Photolysis On Variations Of Diagnostic Binary Ratmentioning
confidence: 99%
“…Despite soot particles were traditionally considered relatively unreactive, this pyrogenic organic matter can indeed be degraded (De la Rosa and Knicker, 2011). Kim et al (2013) showed that soot-associated PAHs can be degraded by photolysis. Energetic UV photons have sufficient energy to disrupt chemical bonds in many materials including soot particles.…”
Section: Introductionmentioning
confidence: 99%